Peran Pendidikan Pancasila dalam Mencegah Radikalisme pada Kalangan Siswa Sekolah Dasar: The Role of Pancasila Education in Preventing Radicalism Among Elementary School Students - Auzi, Cahaya; Saragi, Daulat; Ndona, Yakobus (ITScience (Information Technology and Science), 2024)
The phenomenon of radicalism among teenagers in Indonesia is increasingly worrying, so Pancasila education is one solution to prevent the spread of extreme ideology. This study aims to explore how Pancasila education in elementary schools can play a role in building students' character and preventing radicalization. The research method used is descriptive qualitative, with data collection through interviews, observations, and literature studies. The results of the study indicate that the application of Pancasila values ??in the elementary school curriculum can foster an attitude of tolerance and social awareness among students. Through interactive learning methods, such as group discussions and educational games, students find it easier to understand and internalize these values ??in their daily lives. In addition, the role of teachers as role models is very important in instilling Pancasila values ??in students. Teachers are expected to be able to create a learning environment that supports the development of positive character. However, challenges remain, especially related to the negative influence of social media that can influence students' thinking. Pancasila education must be taught consistently and innovatively to form a strong young generation in facing radical ideology. In conclusion, Pancasila education is not just a subject, but is the foundation for creating a safe and harmonious society. By instilling the noble values ??of Pancasila from an early age, it is hoped that future generations can grow into tolerant individuals who appreciate diversity.